Computerized Dynamic Assessment (C-DA) on Reading Comprehension for L2 Learners of Vocational High Schools - Putri Ismayana; Gunadi Harry Sulistyo; Primardiana Hermilia Wijayati (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study focuses on developing a prototype of an assessment program on reading comprehension based on computerized dynamic assessment. The reading skills to be measure include identifying topic, main idea, the detail of the text, logical inference, an assumption, word meaning and synonym, and a conclusion. The assessment consists of two types of tests including multiple choice type and cloze procedures. Those tests contain prompts as the characteristic of dynamic assessment. The participants in this study were 316 eleventh grade students of vocational high schools. The result reveals that the product was positively agreed by most of the subjects despite the fact that they were not familiar with this assessment program. This indicates that the developed product was acceptable by eleventh grade students on vocational high schools.Abstrak: Penelitian ini fokus pada pengembangan prototipe program penilaian pada membaca komprehensif yang berdasarkan pada computerized dynamic assessment. Kemampuan membaca yang akan diukur pada tes ini, meliputi identifikasi topik, ide pokok, informasi rinci dalam teks, referensi, identifikasi anggapan, memahami makna persamaan kata, dan menyimpulkan. Produk asesmen ini terdiri dari dua tipe teS, yaitu pilihan ganda dan cloze procedures. Tes tersebut mengandung petunjuk/saran sebagai karakteristik dari dynamic assessment. Peserta yang terlibat pada penelitian ini terdiri dari 316 siswa kelas sebelas sekolah menengah kejuruan. Hasil dari pengembangan produk program penilaian computerized dynamic assessment sangat diterima dengan baik dan hampir dari seluruh peserta tidak mengenal program penilaian computerized dynamic assessment. Hal ini mengindikasikan bahwa pengembangan produk ini diterima oleh siswa terutama pada sekolah menengah kejuruan.